SDSS J0909+4449: A large-separation strongly lensed quasar at z ∼ 2.8 with three images. (18th September 2018) - Shu, Yiping; Marques-Chaves, Rui; Evans, N Wyn; Pérez-Fournon, Ismael
ABSTRACT: We report the discovery of SDSS J0909+4449, an exceptional system consisting of a quasar at z  = 2.788 strongly lensed by a group of galaxies at z  ∼ 0.9 into three images separated by up to 14 arcsec based on archival data collected by the Sloan Digital Sky Survey, extended Baryon Oscillation Spectroscopic Survey, Beijing–Arizona Sky Survey, the Mayall z -band Legacy Survey, and the Gemini Telescope. We discuss two hypotheses on the nature of SDSS J0909+4449, i.e. a rare triply imaged quasar in the naked cusp configuration and a typical quadruply imaged quasar with the fourth image undetected in this data. We find that simple lens models can provide excellent fits to the observed image positions and the non-detection under either hypothesis. Deeper imaging data, spectroscopic observations, and follow-up light-curve measurements will be helpful in determining which hypothesis is correct and provide better constraints on the lens mass distribution. Nevertheless, given its unusually large image separations, SDSS J0909+4449 will be a unique probe for the mass structure and the underlying cooling and stellar feedback processes on group or cluster scales.